The Dangerous Days of Daniel X - Patterson, James 1947-; Ledwidge, Michael (New York : Little, Brown, 2008)
Fifteen-year-old Daniel has followed in his parents' footsteps as the Alien Hunter, exterminating beings on The List of Alien Outlaws on Terra Firma, but when he faces his first of the top ten outlaws, the very existence of Earth and another planet are at stake.
Accelerated Reader AR
Keywords: Young adult fiction